AN ANALYSIS OF SEMI DEAD WORDS FOUND IN SUNGAYANG SUB-DISTRICT OF TANAH DATAR REGENCY - Jannahtul Wardiah; Leni Marlina (English Language and Literature, 2017)
This article discusses about Minangkabau language, especially semi dead words that occur in Sungayang District, Tanah Datar, West Sumatra. Semi dead words are words that are almost dead because the younger generation does not understand at all with the words, while the older generation still uses this word for daily communications. The author discusses what words were used by people in Sungayang Sub-district in daily communication, but these words were not used in the colloquial by the people of this district in the present. In writing this article, the authors are assisted by some informants to provide data information about the words that are not used anymore by people in Sungayang Sub-district in the present time. Then the authors grouped the data according to the type and factors causing the occurrence of semi dead words on the words. The results of this study indicate that the lexicons change (lexical change 89.61%) is the type of word that is almost dead (semi dead words) the most dominant in Sungayang district. Contact language (language contact 89.61%) is the most dominant factor of the occurrence of the word almost dead (semi dead words) in Sungayang District.